2019
DOI: 10.1158/1078-0432.ccr-18-3927
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Antibodies Enable Synthetic Agonistic Receptor-Transduced T Cells for Tumor Immunotherapy

Abstract: Purpose: Genetically engineered T cells are powerful anticancer treatments but are limited by safety and specificity issues. We herein describe an MHC-unrestricted modular platform combining autologous T cells, transduced with a targetable synthetic agonistic receptor (SAR), with bispecific antibodies (BiAb) that specifically recruit and activate T cells for tumor killing.Experimental Design: BiAbs of different formats were generated by recombinant expression. T cells were retrovirally transduced with SARs. T-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 46 publications
0
53
0
2
Order By: Relevance
“…Our data are in line with previously published findings showing that the killing mechanism of conventional CARs and the UniCAR system is mainly mediated via the granzyme/perforin pathway, whereas the Fas/FasL axis is also involved. 49,50 Surprisingly, Karches et al 19 published that tumor cell killing caused by their adaptor CAR platform termed SAR was independent from granzyme and perforin release but mainly mediated by FasL. Different killing mechanisms of RevCAR versus SAR that both trigger CD28 and CD3z signals, might maybe also be explained by differences between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are in line with previously published findings showing that the killing mechanism of conventional CARs and the UniCAR system is mainly mediated via the granzyme/perforin pathway, whereas the Fas/FasL axis is also involved. 49,50 Surprisingly, Karches et al 19 published that tumor cell killing caused by their adaptor CAR platform termed SAR was independent from granzyme and perforin release but mainly mediated by FasL. Different killing mechanisms of RevCAR versus SAR that both trigger CD28 and CD3z signals, might maybe also be explained by differences between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several adaptor CAR platforms have been developed. [11][12][13][14][15][16][17][18][19] However, some of them bear the risk for immunogenicity and cross-reactivity if the interacting components are not carefully selected with respect to species compatibility and natural expression pattern in the recipient. 3 Moreover, some of them are not flexible with respect to antigen targeting and guarantee no steering of T cell activity, when the adaptor molecules have a long-term pharmacokinetic half-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a fully murine B cell depletion model, Ma et al demonstrated that B cells repopulated within a short time frame after the termination of CD19-directed FITC adaptor infusion [44]. Several groups further confirmed the functional reversibility of adaptor CAR systems in immunodeficient or competent mouse models, underlining that therapeutic effects can be rapidly re-initiated to control tumor growth in case of tumor relapse (e.g., [44,72,74,80]). In a clinical setting, rapidly eliminated adaptors will facilitate a prompt intervention and fast manipulation of adaptor molecule doses.…”
Section: Controlling Therapy-related Side Effects With Adaptor Carsmentioning
confidence: 99%
“…Although this was the first in vitro data to verify the general functionality of the system, the lytic activity of the redirected FRα CAR T cells against B cell lines was low due to the poor quality of the bsAb adaptors [79]. Later, Karches et al presented alternative bsAb-binding adaptor CARs containing the ECD of human epidermal growth factor receptor variant III (EGFRvIII) or human Cripto-1 and termed them synthetic agonistic receptors (SARs) ( Figure 2i) [80]. In their studies, they explored both tetravalent (2 + 2) and trivalent (2 + 1) bispecific adaptors targeting EpCAM or mesothelin in murine and human mouse models.…”
Section: Bsab-binding Adaptor Carsmentioning
confidence: 99%